Cumulative risks of stent migration and gastrointestinal bleeding in patients with lumen-apposing metal stents - Garcia-Alonso, Francisco Javier; Sanchez-Ocana, Ramón; Peñas-Herrero, Irene; Law, Ryan; Sevilla-Ribota, Sergio; Torres-Yuste, Raúl; Gil-Simón, Paula; de la Serna Higuera, Carlos; Perez-Miranda, Manuel (Endoscopy, 2018)
Background: Delayed gastrointestinal (GI) bleeding and stent migration are known adverse events which may occur following placement of lumen-apposing metal stents (LAMSs). Methods: All consecutive patients who underwent LAMS placement between May 2011 and June 2017 at a single tertiary medical center were included. Demographics and procedural details were prospectively collected. Post-procedure follow-up and outcome measures were retrospectively collected. The cumulative risks of migration and LAMS-related GI bleeding were estimated using the life-table method. Risk predictors were assessed using Cox proportional hazards models.Results: We analyzed 250 patients (64.8 % men; median age 71.6 [interquartile range (IQR) 57.9 – 83.6]). Median follow-up was 78.5 days (IQR 31 – 246.5 days). Thirty-four stent migrations (13.6 %) occurred (5 symptomatic). On multivariable analysis, associations with migration included nasocystic drains (hazard ratio [HR] 6.5, 95 % confidence interval [CI] 2.2 – 19.3), pancreatic fluid collections (PFCs; HR 4.2, 95 %CI 1.8 – 10.1), and double-pigtail stents (HR 2.4, 95 %CI 1.2 – 4.9). Migration risk at 12 months was 25.5 % (95 %CI 17.9 % – 35.7 %) and was higher for PFCs 48.9 % (33.4 % – 66.9 %) than other indications 8.4 % (4.9 % – 17.5 %; P < 0.001). LAMSs placed for longer durations (i. e. enteral anastomoses, biliary and gallbladder drainage) presented an 8.4 % cumulative risk at 2 years. There were 13 LAMS-related GI hemorrhages (5.2 %), two of them fatal, presenting a median of 3 days (IQR 1 – 9 days) after deployment. The cumulative risk of bleeding at 12 months was 6.9 % (3.6 % – 12.7 %). Conclusions: LAMS migration occurs in 1 out of 7 cases and is most common when treating PFCs. Bleeding related to LAMS placement occurs much less commonly but can be life-threatening.